Determining the Drag Resistance of a Little Little - Khakimjonovich, Muradov Rakhimjon (American Journal of Biodiversity, 2025)
As a result of studying the designs of existing seed drills, it was found that they are not suitable for sowing grain seeds in rows between cotton rows. Based on this, a new design of the seeder was selected. In order for the seeder to fully and qualitatively fulfill the tasks set before it, its parameters must be justified. This scientific article is devoted to justifying the parameters of the seeder based on its relationship with the soil.